Subjective, cardiovascular and EMG spectral recovery after lumbar extension exhaustion test - Pereira, Marcelo Pinto [UNESP]; Gonçalves, Mauro [UNESP] (My University, 2008)
The purpose of this randomized study was to evaluate EMG spectral, subjective and cardiovascular recovery parameters after isometric lumbar extension contractions. Ten healthy women performed isometric lumbar extensions until exhaustion with 5%, 10%, 15% and 20% of maximal voluntary isometric contraction on 4 different days (random order). One baseline five second contraction was performed before the fatiguing task which was followed by eight submaximal five second extension contractions (until 20 minutes after the end of the fatiguing task) at the same intensity as the trial to evaluate muscle recovery. EMG (Median Frequency, Peak Power, Peak Power Frequency, Total Power and Zero-crossing Rate) and cardiovascular variables did not demonstrate any statistical difference between the 5-second contractions (p > 0.05) performed before and after the fatiguing task, showing a quick EMG recovery. However, the data analysis showed that the perceived effort variable had not recovered even 10 minutes after the fatigue contraction (p < 0.05). Our results represent a data basis for future comparisons and since subjective felling can affect performance, this study shows the importance of its analysis, since the subjective effort rate was not fully recovered after 10 minutes the end of the exhaustion contraction. © 2008 IOS Press. All rights reserved.
Keywords: Fatigue; Low-back; Recovery; Subjective effort; adult; back muscle; cardiovascular response; clinical trial; controlled clinical trial; controlled study; electromyography; endurance; exhaustion; extensor muscle; female; frequency discrimination; heart rate; human; human experiment; iliocostalis lumborum muscle; lumbar spine; multifidus muscle; muscle fatigue; muscle force; muscle isometric contraction; normal human; priority journal; randomized controlled trial; voluntary movement